Uncontrolled chronic pain: can a pain consultation in primary care be a solution? (Revista Portuguesa de Medicina Geral e Familiar, 2024)
Chronic pain is one of the most frequent medical problems in Portuguese primary health care. These patients significantly show poorer functioning capabilities and quality of life than the general population. The importance of improving the quality of life in patients suffering from chronic pain is paramount, and a holistic approach must be implemented. However, proper pain evaluation and management may be time-consuming in a routine primary health care consultation. Given the significant impact of this disease, we initiated a dedicated consultation for patients with chronic pain in our primary health care unit. A complete evaluation is performed, and, among other questionaries, the Brief Pain Inventory is applied to evaluate pain impact on functioning at the first appointment and re-evaluated after six months of follow-up. In the first six months, 31 patients with uncontrolled pain were referred by their family physicians to this consultation. Non-pharmacological strategies were strongly recommended alongside pharmacological therapies. Although this consultation is relatively recent, our patients with longer follow-ups showed improvement in both maximum and minimum pain levels and substantial improvement in all the measured interferences in the Brief Pain Inventory. Even though there is literature that thoroughly describes the impact of pain on patients’ quality of life, there is much to be done to change this problem. Since family physicians know their patients and their contexts well, they are in a privileged position to manage this problem, and a specific pain consultation in primary health care can be one of the best services for managing pain.
Keywords: Chronic pain; Primary health care; Pain management